MOTIVASI BELAJAR SISWA SMA DITINJAU DARI DUKUNGAN SOSIAL DAN TINGKAT PENDIDIKAN ORANGTUA - Ema Yudiani, RiangGumanti. dan Saeri Tri (LPPM Universitas Proklamasi 45, 2007)
Two hundred and 26 grade 11* student participated on this study in order to understand the relationship between the parent’s social supports, the educational level of father and mother, and the student's motivation to study. This study revealed that the first hypothesis was significant r(226) = .404 i.e. there was relationship between parent’s social supports and student’s motivation to study. The determinant coefficient was also low (16.3%). 1 lowever. the 2